WHO strategies to improve child and adolescents health in Europe - Martin W. Weber; Michelle Black; Susanne Carai; Sophie Jullien (Elsevier, 2024)
Across Europe, the health and wellbeing of children and adolescents requires attention. After the COVID-19 pandemic, the prevalence of mental health conditions has doubled, affecting 1 in 4 adolescents under the age of 18. Overweight and obesity are increasing: 1 in 3 primary school children are overweight or obese. Inequalities in weight and mental health are increasing in many countries, driven by socioeconomic circumstances. Reduction in child mortality, particularly of neonates, is stagnating in several countries, especially in Eastern Europe and Central Asia, and reversing in some.To rally member states to action, WHO is developing a new regional Child and Adolescent Health Strategy. The development commenced in 2019 with the identification of problem statements of issues affecting children and adolescents. These were then converted into actionable standards. They were updated considering the COVID-19 experience and the effects of regional crises on children. Children and adolescents were engaged in the development of the strategy, to identify and take their priorities into account, and stakeholders inside and outside WHO were consulted, including pediatricians and their societies. During a Member States consultation, European countries will have the opportunity to review and revise the draft strategy before it will be presented to the WHO Regional Committee for Europe for adoption.The main components of the strategy are: Early childhood development, school and adolescent health, strengthening health systems and improving quality of care, recognizing and acting on the needs of the most vulnerable and galvanizing societal action on the commercial, social, environmental and digital determinants of health affecting children and adolescents.The strategy forms the basis for monitoring regional progress. It will enable the development of national child and adolescent health and wellbeing strategies and monitoring frameworks. The implementation of the strategy will enable children and adolescents to realize their right to physical, social and mental health and well-being in healthy and enabling environments, so that they can fully participate in shaping prosperous and sustainable societies.